PENGGUNAAN ALAT PERAGA PEMBURU BATA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI BANGUN DATAR - satria, satria; Purnamasari, Ita; Putri, Siti Khadijah (JURNAL E-DUMATH, 2015)
The purpose of this study was to determine the increase in the use of props proof formula Build Size Flat ( PEMBURU BATA ) on learning outcomes of fourth grade students in an elementary school in Tangerang. The research method used is the method of comparison with intact -group research design is pre - experimental designs ( nondesigns ) . The samples were the fourth grade at an elementary school in Tangerang academic year 2014/2015 totaling 28 students. The instruments used were pretest , posttest , and motivation questionnaire . Based on the analysis results obtained are acceptable so props H0 PEMBURU BATA can not improve student learning outcomes of fourth grade at an elementary school in Tangerang . So PEMBURU BATA props less effective in improving student learning outcomes in four grade on the material flat wake at a primary school in Tangerang.